Rumah Solehah - Malaysia: Half Way Home For Women And Children With HIV/AIDS (Bangladesh Journal of Medical Science, 2009)
Rumah Solehah (RS) is a half way home for women and children living with HIV/AIDS. Since July 1998, more than 100 women and 50 children have "graduated" from RS. Presently, we have 22 children, 3 months to 9 years old and 8 women. We bought our own home in Kampung Pandan in 2007. We have a second home in Cheras and started a third home in Kuala Terengganu in August 2007. The home and family ambience of RS has offered our women and children the opportunity to cherish the joy and happiness of family life and caring for each other. RS received the Tun Dr. Siti Hasmah Special Mention Award 2004 for excellence in care and support at the grass-root level. With the inevitable surplus of HIV/AIDS infected and affected children, the challenges to RS will continue to be a daunting and awesome one. Together we can make a difference to the lives of these little and innocent souls. doi: 10.3329/bjms.v8i1.3187 Bangladesh Journal of Medical Science Vol.8 No. 1-2; 2009 29-32